Quality Improvement and Participation in Perinatal Quality Collaboratives Promote Patient Safety. Issue 3 (May 2022) - Simpson, Kathleen Rice
Abstract : In August 2021, the Centers for Medicare and Medicaid Services issued new requirements for hospitals with maternity services to report participation in perinatal quality collaboratives and adoption of perinatal patient safety bundles. A summary of the requirements and implications for practice is provided.